PERAN PATROLI RODA DUA DALAM MENCEGAH KEJAHATAN PENCURIAN DENGAN PEMBERATAN OLEH SATUAN SABHARA POLRES BANTUL - Lukas Satputro (Advances in Police Science Research Journal, 2019)
This research is motivated by the high number of cases oftheft in Bantul Regency, especially in 2018 - 2020. In the context of preventing the crime of theft by weight, efforts are made through two-wheeled patrol units. Turjawali Sabhara Unit of Bantul Police. The purpose of the study was to determine the implementation of patrols in preventing the crime of theft by weighting, knowing the factors that affect the implementation of patrols and the efforts made to prevent the crime of theft by weighting. The results of the study found that the implementation of patrols which were analyzed with Article 22 of Perkabaharkam Number 1 of 2017 was still not carried out properly. This was caused by several obstacles, including the lack of skills of patrol members in the field of patrol and division of tasks within the Sabhara Unit which was too focused on the Dalmas platoon and patrol operational vehicles, especially two-wheelers, most of which were in damaged condition, either lightly or heavily damaged, thus requiring repair. The conclusion is that the role of patrols in the community has not been seen in preventing the crime of theft by weighting that occurred in Bantul Regency, there are six factors that influence it, namely four supporting factors and two inhibiting factors. The suggestions are (1) Kasat Sabhara should review the division of duties of the Sabhara Unit personnel and conduct training for patrol members using methods from personnel for personnel regarding the field of patrol and community policing (2) Kasat Sabhara is expected to be able to urge patrol members regarding vehicle maintenance so that vehicles indication of damage can immediately be anticipated without having to undergo repairs in the workshop.